Marketing Platform as Promotion Tool in Business - Putri, D A; Kurniasih, Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to describe, analyze, and determine the role of social media in marketing strategies. This research used a survey method that is focused on people who are in a business that is in direct contact with social media so that it can be reviewed directly on the role of social media in marketing strategies. The implementation of social media in marketing strategies has been implemented by several companies or other business entities to market their products. Various content and network contacts are the principles behind social media. The utilization of social media itself has been done for various purposes, one of which is to do business. Businessman utilizes social media because it is considered more efficient in time and cost. Moreover, almost all people in various parts of the world use social media to support daily activities such as communicating and exchanging information. The results of this research show that social media has a significant role in marketing strategies for small- and large-scale businesses. That condition because of the ease of disseminating information and also greater efficiency in marketing activities.